Absorption and antidysryhthmic activity of oral disopyramide phosphate after acute myocardial infarction - Kumana, Cyrus R. (1982)
1 In a prophylactic, double-blind, randomized placebo-controlled trial of oral disopyramide phosphate, initiated within 12 h of suspected acute myocardial infarction (MI), antidysrhythmic effect was evaluated. The loading dose was 150, 200, or 300 mg followed 6 h later by 100, 150, or 200 mg every 6 h for patients assessed to weigh <55, 55-85, or >85 kg, respectively. After each loading dose and a maintenance dose on one of days 4-7, 2 and 6 h venous blood samples were obtained for determination of plasma disopyramide and mono-N-dealkylated disopyramide (MND) concentrations (expressed herein as levels), by a technique incorporating fluorescence photometry and thin layer chromatography. Of 121 patients entering the trial, 101 had confirmed acute MI and of these, 12 on active drug were recalled during convalescence and restudied after a loading dose. 2 In acute MI patients on disopyramide phosphate, an important degree of antidysrhythmic effect was observed (on active drug and placebo, 19% v 37%, respectively (P = 0.047), received lignocaine for `warning arrhythmias'), even though in the first 6 h post-loading dose, disopyramide and MND levels were low and variable. 3 Disopyramide levels 2 h post-loading dose were lower in acute MI than in non-MI patients (P = 0.004), and similarly in the limited within patient study corresponding levels after acute MI were lower than during convalescence (P = 0.013). At 6 h post-loading dose, the levels had increased in acute MI patients but decreased in non-MI patients, this change being significantly different (P = 0.048). A similar significant difference existed in the limited within patient data available during acute MI and convalescence (P = 0.002). 4 Acute MI patients on active drug developing `warning arrhythmias' had lower post-loading dose, 2 and 6 h levels than in those without `warning arrhythmias' (P = 0.012 and P = 0.0002, respectively). 5 One patient who developed renal insufficiency developed excessive disopyramide levels. 6 On any given dose, there was no significant correlation between disopyramide level and body weight. 7 In acute MI patients given oral disopyramide phosphate (a) there was marked interindividual variation in the ensuing drug and metabolite levels, (b) absorption of disopyramide into the circulation was delayed, (c) prophylactic antidysrhythmic activity was present at levels of about 1.5 mg/l which is about half the minimal level recommended hitherto, (d) disopyramide accumulated in renal insufficiency, (e) elaborate dosage adjustments based on body weight are not useful.